2021
DOI: 10.1007/s10637-021-01137-y
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology of triptolide in cancer cells: implications for transcription factor binding

Abstract: SummaryBackground Triptolide is an active natural product, which inhibits cell proliferation, induces cell apoptosis, suppresses tumor metastasis and improves the effect of other therapeutic treatments in several cancer cell lines by affecting multiple molecules and signaling pathways, such as caspases, heat-shock proteins, DNA damage and NF-ĸB. Purpose We investigated the effect of triptolide towards NF-ĸB and GATA1. Methods We used cell viability assay, compare and cluster analyses of microarray-based mRNA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The generation of cluster image maps (CIMs) or so-called heat maps was pioneered by a consortium of the Harvard Medical School, NCI (Bethesda, MD, USA), and other research institutes [ 59 , 60 ]. In the past years, we investigated this concept for natural products (e.g., [ 61 , 62 , 63 ]). Rather than transcriptomic mRNA expression, we focused on proteomics in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of cluster image maps (CIMs) or so-called heat maps was pioneered by a consortium of the Harvard Medical School, NCI (Bethesda, MD, USA), and other research institutes [ 59 , 60 ]. In the past years, we investigated this concept for natural products (e.g., [ 61 , 62 , 63 ]). Rather than transcriptomic mRNA expression, we focused on proteomics in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…TP has been found to exert a role in cancer by targeting a variety of molecules (Seo et al., 2021). Previous studies had reported that TP inhibited breast cancer growth by targeting HMGB1 (Jiang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most terpenoids are isolated from medicinal plants that belong to the following plant groups: Oleaceae, Rutaceae, Labiatae, Acanthaceae, Compositae, Taxaceae, Pinaceae, Lauraceae, Araliaceae, Celastraceae, etc. Terpenoids are classified according to the number of isoprene (2-methylbuta-1, 3-diene) units into monoterpenoids (C 10 ), Menthol Peppermint oil (Mentha piperita) [17] Myrcene bay laurel oil (Laurus nobilis) and Verbena oil (Lippia citriodora) [18] Perillyl alcohol [19] Eucalyptol (1.8-cineole) Eucalyptus leaf oil (Eucalyptus globules), rosemary (Rosmarinus officinalis) [20] Sesquiterpenoids Artemisinin and its derivatives Sweet wormwood (Artemisia annua) [21] Costunolide Aucklandia lappa [22,23] Diterpenoids Acanthoic acid Acanthopanax koreanum Nakai, Croton oblongifolius Roxb [24,25] Oridonin Rabdosia rubescens [26] Tanshinone IIA Salvia miltiorrhiza Bge [27] Taxol (Paclitaxel) Taxus brevifolia [28] Triptolide Tripterygium wilfordii [29,30] Kaurenoic acid Annona senegalensis (Annonaceae) [31] Triterpenoids Celastrol Tripterygium wilfordii [29] Withaferin A Withania somnifera [32] Ursolic acid Rosmarinus officinalis (rosemary), Calluna vulgaris and Eugenia jambolana, Salvia officinalis, and Eriobotrya japonica [33] Tetraterpenoids Lycopene Tomatoes (Lycopersicon esculentum), pink guavas, apricots, water melon, and pink grapefruits [34,35] Lutein Spinach, kale, carrot, corn, and egg yolk [36,37] β-carotene Carrot [38] sesquiterpenoids (C 15 ), diterpenoids (C 20 ), triterpenoids (C 30 ), tetraterpenoids (C 40 ), and polyterpenoids (C > 40) [Table 1]. They possess vast medicinal importance that includes: antitumor, antibacterial, antimalarial, anti-inflammatory, antiviral, anticancer, immunomodulatory, anti-aging, antioxidant, anti-depressants, antifungal, and antidiabetic.…”
Section: Terpenoidsmentioning
confidence: 99%
“…Its anticancer action is by inducting mitotic arrest through the targeting of the cytoskeleton component tubulin, resulting in mitotic activation and apoptosis. [30] It is used to treat pancreatic, ovarian, and breast cancers.…”
Section: Paclitaxelmentioning
confidence: 99%